You wouldn't want to be a Roman gladiator! : gory things you'd rather not know - Malam, John, 1957-; Antram, David, 1958-; Salariya, David (New York : Franklin Watts, 2013)
A light-hearted introduction to the life and training of a Roman gladiator.
Includes index.
4.5
3-6
Keywords: Rome -- Civilization -- Juvenile literature; Gladiators -- Juvenile literature; Rome -- Civilization; Gladiators; Rome -- Civilization; Gladiators